Persepsi Masyarakat Terhadap Dampak Pembangunan Pelabuhan Bungkutoko Pada Ekosistem Mangrove di Kelurahan Bungkutoko Kecamatan Abeli Kota Kendari - Sarman, Sarman; Limi, Muhammad Aswar; Fyka, Samsul Alam (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2019)
This study aims to determine the public perception of the impacts arising from port  development activities in the mangrove ecosystem with the number of samples  using  Proportional  Stratifield Ramdom Sampling as many as 22 people. The results of the study show that the economic activities of the development of population ports can cause damage to the mangrove forest ecosystem in Bungkutoko Sub-District, Abeli District, Kendari City, from the construction of ports in the mangrove forest area, the number of marine biota inhabiting mangrove forests has been reduced due to the decrease in water quality in the area around the port. Conservation efforts are carried out through conservation, rehabilitation and reforestation by the government and the community, as in August 2, 2018, the Government together with the Muspika and the heads of RT / RW and village heads and the community, worked together to plant mangroves in the coastal area. Mutual cooperation is also a determination to save the mangrove forest area. This was done for the rescue and preservation of the mangrove forest ecosystem in Bungkutoko Village, Abeli District, Kendari City. The replanting is done in the initial stages, then cleaning up the garbage scattered in the mangrove forest area to make it look beautiful again